A Trend Analysis of Changes in Cooling Degree Days in West Africa Under Global Warming - Kagou Dicko; Emmanuel Tanko Umaru; Souleymane Sanogo; Appollonia Aimiosino Okhimamhe; Ralf Loewner (Atmosphere)
Monitoring energy consumption in response to rising temperatures has become extremely important in all regions of the globe. The energy required for cooling is a major challenge in West Africa, where the climate is predominantly tropical. Among the various methods for evaluating energy requirements, the degree-day method is best known for its ability to estimate the heating, ventilation, and air-conditioning (HVAC) requirements of buildings. This study used three decades of weather station data to assess the cooling degree days (CDD) in two major West African cities, Kano and Bamako, across a range of base temperatures from 22 °C to 30 °C. The results indicate an increase in cooling degree days for Kano, whereas Bamako experienced a decrease in these parameters over the same period. Nonetheless, Bamako required a relatively higher cooling demand for all base temperatures. Furthermore, the study showed that the years 1998 and 2015 had the most significant impact on Kano and Bamako, with CDD values ranging from 2220 °C-day to 218 °C-day for Kano and from 2425 °C-day to 276 °C-day for Bamako. The study also found that a lower base temperature leads to higher energy consumption, while a higher base temperature leads to lower energy consumption. This information provides a useful reference for governments and policymakers to achieve energy efficiency and reduce greenhouse gas emissions.